2014
DOI: 10.1002/jclp.22136
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Intentional Self‐Injurious Behavior and the Loudness Dependence of Auditory Evoked Potential in Research Volunteers

Abstract: The LDAEP has the potential to be used as a noninvasive index of intentional self-harm disposition. Additional studies are needed using other populations, including women and treatment-seeking individuals, to determine if the LDAEP more broadly discriminates risk of self-injuring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…A study among a patient sample also did find not any differences in the LDAEP between those of varying levels of suicide risk ( g = - 0.23; Graßnickel et al, 2015). In contrast, one study among a sample of male undergraduates found a positive relationship between the LDAEP and Suicidal Behaviors Questionnaire scores ( g = 0.14; Marsic et al, 2015).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…A study among a patient sample also did find not any differences in the LDAEP between those of varying levels of suicide risk ( g = - 0.23; Graßnickel et al, 2015). In contrast, one study among a sample of male undergraduates found a positive relationship between the LDAEP and Suicidal Behaviors Questionnaire scores ( g = 0.14; Marsic et al, 2015).…”
Section: Resultsmentioning
confidence: 83%
“…To date, only two studies have examined the LDAEP and how it may differ in those with SI. The first, a study of college students and community members, did not find a relationship between the LDAEP and self-reported SI ( g = 0.31; Marsic, 2012). The second study recruited two groups of patients: (1) patients with depression with atypical features and (2) patients with depression without atypical features (Lee et al, 2014).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The P2 was defined as the second positive-going wave captured at electrode sites over the fronto-central or parieto-occipital regions. The time window for the younger participants was set at 150–230 ms, based on the waveform observed in this study and the time windows reported in previous studies (Liu et al, 2014 ; Marsic et al, 2015 ). The time window for the older participants was set at 190–270 ms (40 ms delay), which was based on the results of previous studies demonstrating a delayed onset latency of P2 due to the aging effect (Martin and Jerger, 2005 ; Ross et al, 2007 ; Ozmeral et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Another study investigated the relationship between the LDAEP and self-injurious behavior. 28 The LDAEP was measured in 41 men, who then completed the Suicidal Behaviors Questionnaire (SBQ) and the Deliberate Self-Harm Inventory (DSHI). The LDAEP was positively correlated with scores on the SBQ and DSHI.…”
Section: Ldaep and History Of Suicide Attempts In Patients With Mddmentioning
confidence: 99%